2014
DOI: 10.1111/geb.12158
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted diversity–area relationships reveal global hotspots of mammalian species, trait and lineage diversity

Abstract: The fact that PD/FD reach faster their maximal value than SR may suggest that the two former facets might be less vulnerable to habitat loss than the latter. While this point is expected, it is the first time that it is quantified at global scale and should have important consequences in conservation. Incorporating species relative coverage into the delineation of multifaceted hotspots of diversity lead to weak congruence between SR, PD and FD hotspots. This means that maximizing species number may fail at pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
127
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 49 publications
3
127
0
5
Order By: Relevance
“…Global priority regions for mammal conservation have been identified (9,10,28,29), but few have included different [i.e., taxonomic, phylogenetic, and functional (15,21)] dimensions of mammal biodiversity simultaneously, and few have used a complementarity-based prioritization framework globally (30)(31)(32)(33). Further, all prioritization analyses for mammals incorporate taxonomic, phylogenetic, and functional information by using alpha diversity indexes (15,21,23).…”
Section: Significancementioning
confidence: 99%
See 4 more Smart Citations
“…Global priority regions for mammal conservation have been identified (9,10,28,29), but few have included different [i.e., taxonomic, phylogenetic, and functional (15,21)] dimensions of mammal biodiversity simultaneously, and few have used a complementarity-based prioritization framework globally (30)(31)(32)(33). Further, all prioritization analyses for mammals incorporate taxonomic, phylogenetic, and functional information by using alpha diversity indexes (15,21,23).…”
Section: Significancementioning
confidence: 99%
“…For example, species richness was an effective surrogate for the functional and phylogenetic dimensions of local rodent assemblages in Manu (25). In contrast, Mazel et al (15) identified strong geographical mismatches among global hotspots of taxonomic, phylogenetic, and functional diversity of mammals. Low geographical congruence was also found in prioritization analyses based on taxonomic, phylogenetic, and trait diversity of birds and mammals in Brazil (21).…”
mentioning
confidence: 96%
See 3 more Smart Citations